Assessing effect of behaviour change on HIV/AIDS prevalence using a staged progression model - Pfupajena, Mandidayingeyi H.; Mashiri, Chiedza E.; Mashasha, Maxwell; Mlilo, Vusimusi; Gonzo, Loyce; Maposa, Susan; Chandiwana, Edina; Mukwembi, Pauline (Midlands State University, 2016)
A staged progression model was proposed that is an intervention model incorporating behaviour change. Analysis of the intervention model revealed that the disease free equilibrium point is locally stable when the bifurcation parameter β < β * near R0 = 1. The endemic equilibrium point was shown to be locally stable using the centre manifold theorem and a Lyapunov function was used to show that the endemic equilibrium point is globally asymptotically stable. Results suggest that positive behaviour change is effective in reducing the HIV/AIDS prevalence for the first few years suggesting that positive behaviour change alone cannot be used effectively to control or eradicate HIV/AIDS. In the case of negative behaviour it was seen that negative behaviour change negatively impacts the population greatly during the first few years of the onset of the disease. However changes in patterns of HIV prevalence in Zimbabwe and most developing countries are quite recent and caution is required on the representativeness of the estimates and to note whether the observed changes are consistent with behaviour change and not the natural course of the HIV epidemic.